Involvement of the intermediate nucleus of the lateral septal area on angiotensin II-induced dipsogenic and pressor responses - Freiria-Oliveira, Andre H. [UNESP]; Blanch, Graziela T. [UNESP]; Camargo, Luis A. A. [UNESP]; Menani, José Vanderlei [UNESP]; Saad, Wilson A. [UNESP] (Elsevier B.V., 2009)
Previous studies have shown that different parts of the septal area may have opposite roles in the control of water intake and cardiovascular responses. In the present study we investigated the effects of electrolytic lesions of the intermediate nucleus of the lateral septal area (LSI) on cardiovascular and dipsogenic responses to intracerebroventricular (icv) angiotensin II (ANG II) and water intake induced by other different stimuli. Male Holtzman rats (280-320 g of body weight, n = 6-16/group) with sham or electrolytic lesions of the LSI and a stainless steel cannula implanted into the lateral ventricle (IV) were used. The LSI lesions did not affect body weight or daily water intake. However, LSI lesions reduced water intake and pressor responses induced by icv ANG II (4.10(-2) nmol). The LSI lesions also slightly reduced water intake induced by 24 h of water deprivation or isoproterenol (30 mu g/kg) subcutaneously, but did not affect water intake induced by intragastric 2 ml of 2 M NaCl load. The results suggest that LSI is part of the forebrain circuitry activated by ANG II to produce pressor and dipsogenic responses. However, the same nucleus is not involved in the dipsogenic responses to central osmoreceptor activation. (c) 2009 Elsevier B.V. All rights reserved.
Keywords: Water intake; Hypertension; Thirst; Arterial pressure; Water deprivation